Effect of dimensionality on the spectra of hybrid plasmonic-photonic crystals - Romanova, Alexandra; Korovin, A. V.; Romanov, Sergey (Physics of the Solid State, 2013)
Based on colloidal crystals of various dimensionality, hybrid metal-dielectric plasmonic-photonic heterocrystals have been prepared. It has been shown that the spectra of optical transmission of heterocrystals are mostly controlled by the sum of contributions of composing plasmonic and photonic crystals. At the same time, there are a number of phenomena caused by the mutual effect of heterostructure components, which lead to a deviation of observed optical properties from the linear superposition of responses of these crystals. In particular, it has been found that the anomalous transmission controlled by the plasmonic crystal decreases with increasing the dimensionality of the photonic crystal attached to it. At the same time, light reflection on a metallized surface changes light diffraction in photonic crystals and leads to Fabry-Perot oscillation amplification. It has been assumed that an intermediate layer is formed, in which Bloch modes of the photonic crystal and surface plasmon-polaritons of the plasmonic crystal are hybridized.
EAM Import::2019-03-14